THE INFLUENCE OF DESTINATION IMAGE AND PERCEIVED VALUE ON SATISFACTION OF LITERACY PARK - Yunita, Sherly; Tjokrosaputro, Miharni (Graduate Program of Universitas Tarumanagara, 2024)
The public's low interest in reading has caused Indonesia to become one of the countries with the lowest literacy rate in the world. Literacy is an activity that includes skills in reading and writing, skills in interpreting information used for the development of education, development and quality human resources.This research has the purpose to determine the influence of destination image and perceived value on satisfaction. The research method used was a survey with data collection through a questionnaire distributed to 251 respondents by using purposive sampling. The measurement scale in this study used a 5-point Likert scale.The analysis of the variance-based SEM method, PLS-SEM, shows that destination image significantly affects satisfaction and perceived value significantly. This research aims to positively contribute to advancing the tourism industry, especially in a literacy park destination, bolster sustainable government policies, and shape visitors loyalty towards literacy park. The study results provide the implication that destination image and perceived value have an important role in shaping visitors satisfaction. Besides that, this research uses variables rarely used in the tourism industry to measure satisfaction. This research proves that destination image and perceived value have a positive and significant relationship to satisfaction. This research's empirical basis and findings can serve as a reference for future studies. This research was conducted to strengthen research regarding destination image variables, perceived value, satisfaction and destination loyalty in a tourist destination, especially the Martha Christina Tiahahu Literacy Park. It is also hoped that this research can contribute to increasing literacy activities in Indonesia. It is hoped that the results of this research can be used as material for innovation and evaluation by marketers in managing destinations. Apart from that, it is hoped that the results of this research can also provide input for similar tourist destinations in increasing visitor loyalty.